Validation Tests of Resuspension Models for a Finite and Infinite Site. Issue 4 (October 2019) - Whicker, Jeffrey J.; McNaughton, Michael; Ruedig, Elizabeth; Fuehne, David P.
Abstract : Abstract: Dose assessment for deposited radionuclides often requires estimates of air concentrations that are derived from measured soil concentrations. For this, dose assessors typically use literature resuspension values that, while empirically based, can vary by orders of magnitude making it difficult to provide accurate dose estimates. Despite the complexities of the physical processes involved in resuspension, the models generally used for dose assessment are relatively simplistic and rarely are the models validated for a specific site, thus making prediction of air concentrations or airborne emissions highly uncertain. Additionally, the size of the contaminated area can have an impact on downwind concentrations, yet literature values do not account for smaller-sized contaminated sites adding additional uncertainty. To test resuspension models for soil-bound radionuclides at finite and infinite spatial scales, measurements of soil and air concentrations are made at (1) a location downwind of a former outfall where 239 Pu was released into the environment (a finite site), and (2) uncontaminated locations where regional air sampling provides background measurements of naturally occurring 238 U in sampled dust (an infinite site). Measured air concentrations were compared to those predicted using the resuspension factor model and the mass loading model. An area factor was applied to the smaller contaminated site to account for dilution of dust from the contaminated site with dust originating from offsite locations. Results show that when properly parameterized to site conditions, resuspension models can predict air concentrations to within a factor of 10.